ADVANCED CARDAN PROPELLER SHAFT JOINT - Vinayak Bapat; Vaibhav Bhosale; Saurabh Dhotre; S. S. Jadhav; Baburao Suryawanshi (International Journal of Innovations in Engineering Research and Technology, 2022)
In any direct mechanical drive system, there exists a need to couple the variety of driven elements that may be included. The majority of drive elements, including gear reducers, lead screws, and a host of other components, are driven by shafting that is supported by multiple bearings. This allows for shafting to be held extremely straight and rigid while rotating, avoiding any possible balancing and support problems. Because of this rigid support, it is virtually impossible to avoid slight misalignments between a driving and driven shaft when they are connected. Restoring forces that occur as the two coupled shafts compete to maintain their original positions can put unwanted strain on shaft bearings, causing them to wear out prematurely. Additional axial loads are also placed on the bearings as thermal growth occurs in shafting during operation. The basic function of a power transmission coupling is to transmit torque from an input shaft to an output shaft at a given shaft speed and, where necessary to accommodate shaft misalignment. Misalignment is the result of many factors including installation errors and tolerance variations. Shaft misalignment can increase the axial and radial forces exerted on the coupling.These side loads result from dynamic coupling behavior, frictional loads and loads caused by flexing or compressing coupling components. The undesirable results include tensional or angular velocity vibrations which reduce system accuracy, excessive forces and heat on system bearings which reduce machine life, increased system vibration and noise which adversely affects equipment operation. The solution to the above problem is an indigenous coupling that gives constant transmission of torque and angular velocity. The main features of the coupling being minimize or even eliminate side loads, higher shaft misalignment capabilities, greater drive accuracy.